Oriente Moderno (JSTOR)
The journal Oriente Moderno was established in 1921 by Carlo Alfonso Nallino who was its director until his death in 1939. Some of the most prominent Italian scholars on the Muslim world have succeeded him: Ettore Rossi (who later on gave his books and documents to the Institute) and Paolo Minganti. The Journal has been directed by Prof. Claudio Lo Jacono since 1995.
Keywords: African Studies